Don’t shoot me I’m only the transport planner (apologies to Sir Elton John) - Kenworthy, Jeffery (Eco-Logica Ltd, 2012)
An historical review of the origins, underlying philosophy, development, use and abuse of land use-transport or traffic models is provided. It is argued that the way these models have been used, and often still are used today, has resulted in extreme automobile dependence with its associated negative social, environmental and economic impacts. Contrasting responses to the predictions from such traffic models in cities around the world are reviewed. The many failures of these models at both a strategic and technical level are discussed. The paper then outlines how cities might respond to the shortcomings of traditional transport planning which uses such models. A key underpinning of the paper is the idea that transport planning can no longer be based on a ‘predict and provide’ approach, which treats traffic as a liquid. Rather, communities must adopt visioning processes based on a ‘debate and decide’ approach, which treat traffic as a gas that expands and compresses according to how much road space is provided for it.